2015
DOI: 10.1002/2015jd023491
|View full text |Cite
|
Sign up to set email alerts
|

The microphysical pathway to contrail formation

Abstract: A conceptual framework to predict microphysical and optical properties of contrail particles within a wingspan behind the source aircraft is developed. Results from two decades of contrail observations and numerical simulations are reviewed forming the basis of theoretical model development. The model utilizes cloud theory applied to the dynamics and thermodynamics of jet aircraft exhaust plumes in upper tropospheric conditions. Droplet nuclei include soot particles emitted from aircraft engines and atmospheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
122
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(159 citation statements)
references
References 75 publications
7
122
1
Order By: Relevance
“…Plume aerosol particles have varying sizes and properties with larger and more hygroscopic particles activating into droplets first (Köhler, ) depleting supersaturation ( s w ). The basic assumption of the parameterization of Kärcher et al () is that all droplets in the rapidly cooling plume form at the same time, ( t o ), at the “activation relaxation time.” The parameterization determines the droplet number concentration ( n(t o ): = n o ) which is needed to balance a further increase of s w by condensation loss. This implies two approximations: The first one is that quenching of s w is assumed to occur instantly since the remaining smaller and less hydrophilic particles cannot be activated any more once s w is decreasing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plume aerosol particles have varying sizes and properties with larger and more hygroscopic particles activating into droplets first (Köhler, ) depleting supersaturation ( s w ). The basic assumption of the parameterization of Kärcher et al () is that all droplets in the rapidly cooling plume form at the same time, ( t o ), at the “activation relaxation time.” The parameterization determines the droplet number concentration ( n(t o ): = n o ) which is needed to balance a further increase of s w by condensation loss. This implies two approximations: The first one is that quenching of s w is assumed to occur instantly since the remaining smaller and less hydrophilic particles cannot be activated any more once s w is decreasing.…”
Section: Methodsmentioning
confidence: 99%
“…Dry core radii r act,l of each particle type l that can activate into water droplets at certain plume supersaturation s w are obtained from Kappa‐Köhler theory (Petters & Kreidenweis, ) by ritalicact,l=rK427ln2swκl3, where r K ~1 nm is the fixed Kelvin radius and κ l denotes the hygroscopicity parameter characterizing the water uptake and activation behavior of the particle type l depending on its chemical composition. Please note that we use the parameterization from Kärcher et al () but we calculate the dry core radius for activation according to Petters and Kreidenweis (). This means that we keep the factor 4/27 under the third root consistent with prescribing the Kelvin radius.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that changes in particulate emissions, such as soot, were not taken into account. A reduction in the soot number densities from lean combustion would result in changes of the properties of the contrails (lower ice particle densities, lower shortwave optical thickness, and enhanced sedimentation of ice particles), which would lead to a much larger decrease of the climate impact by contrails [136][137][138]. A detailed description of the study can be found in [135].…”
Section: Strategic Technological Measure: Strut-braced Wing Aircraft mentioning
confidence: 99%
“…One remaining unknown pointed out in the latter work is the role played by ultrafine droplets consisting of organics. The problem of nucleation of ice particles in contrails was recently revisited by Kärcher et al (2015).…”
Section: Nucleationmentioning
confidence: 99%